The current state of scientific elaboration of using means of operative and search activities in combating crime (Bulletin of Kharkiv National University of Internal Affairs, 2018)
Research papers from different areas of legal science, which are split by time criterion have been analyzed. Thus, the authors has considered the research conducted in the Soviet period, the subject of which were different aspects of using means of operative and search activities. In particular, having analyzed the research of the stated period, the author has highlighted two areas to study specified issues: those that were conducted within forensic science and the science of operative and search activities. At the same time it has been stressed that all Soviet textbooks, monographs, candidate dissertations and other types of works that were devoted to the study of general aspects of operative and search activities or combating different types of crime, considered in most cases the use of special means, including operative and search. Comparing the works of Soviet and modern Ukrainian experts, the author has made a similar conclusion in the part relating to the research of using means of operative and search activities. However, analyzing the domestic research devoted to the outlined problems, the author of the article states that the studies mostly use outdated regulatory base and does not take into account the latest technological achievements, although national experts in the field of operative and search activities consider the topic of using means of operative and search activities while studying general theoretical issues of operative and search activities.As the result of the study the author has stated that the use of special means of operative and search activities has basically been the subject of research of specialists in forensic and operative and search activities spheres. However, it has been summarized that nowadays there are no current fundamental scientific works, where the issue of using means of operative and search activities in combating crime would be considered in dissertations and monographs.